Benchmarking numerical models of brittle thrust wedges. (November 2016) - Buiter, Susanne J.H.; Schreurs, Guido; Albertz, Markus; Gerya, Taras V.; Kaus, Boris; Landry, Walter; le Pourhiet, Laetitia; Mishin, Yury; Egholm, David L.; Cooke, Michele; Maillot, Bertrand; Thieulot, Cedric; et al.
Abstract: We report quantitative results from three brittle thrust wedge experiments, comparing numerical results directly with each other and with corresponding analogue results. We first test whether the participating codes reproduce predictions from analytical critical taper theory. Eleven codes pass the stable wedge test, showing negligible internal deformation and maintaining the initial surface slope upon horizontal translation over a frictional interface. Eight codes participated in the unstable wedge test that examines the evolution of a wedge by thrust formation from a subcritical state to the critical taper geometry. The critical taper is recovered, but the models show two deformation modes characterised by either mainly forward dipping thrusts or a series of thrust pop-ups. We speculate that the two modes are caused by differences in effective basal boundary friction related to different algorithms for modelling boundary friction. The third experiment examines stacking of forward thrusts that are translated upward along a backward thrust. The results of the seven codes that run this experiment show variability in deformation style, number of thrusts, thrust dip angles and surface slope. Overall, our experiments show that numerical models run with different numerical techniques can successfully simulate laboratory brittle thrust wedge models at the cm-scale. In more detail, however, we find that it is challenging to reproduce sandbox-type setups numerically, because of frictional boundary conditions and velocity discontinuities. We recommend that future numerical-analogue comparisons use simple boundary conditions and that the numerical Earth Science community defines a plasticity test to resolve the variability in model shear zones. Highlights: A quantitative comparison of thrust wedge models of 11 codes and 15 laboratories. Similarity in results encourages using both methods for natural thrust wedge studies. The numerical Earth Sciences community needs a test for brittle material behaviour.